Violenza di genere, stranieri e servizi assistenziali. Un’indagine etnografica sulle rappresentazioni degli operatori e delle operatrici professionali - Zecca Castel, Raúl (Antropologia Pubblica, 2024)
This article presents the results of an ethnographic research conducted within the framework of the project “Families. Rinforzare i legami territoriali per sostenere famiglie vulnerabili” (Strengthen territorial ties to support vulnerable families), funded by the Asylum, Migration and Integration Fund (FAMI 2014-2020). The survey aimed at detecting the operators’ socio-cultural representations of gender-based violence within the interinstitutional anti-violence network in the Territorial Areas of Treviglio and Romano di Lombardia (province of Bergamo), where the project was activated. Data collected via ethnographic method (questionnaire surveys, semi-structured interviews, and focus-group meetings) have highlighted some weaknesses and potentially prejudicial criticalities for the fulfillment of the mandate to which professional operators are called for, especially when users with foreign backgrounds are involved. The article unravels the ethnographic results and attempts at sketching out some suggestions for the creation and implementation of a more effective user-oriented framework of intervention, targeting the victims of gender-based violence.